1954
DOI: 10.1001/jama.1954.03690260004002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Significance of Bleeding in Early Pregnancy

Abstract: consequences of the combination of anoxia and a high level of circulating epinephrine on cardiac function can be produced both in the operating room and the labo¬ ratory. The fearful patient subjected to a hurried induc¬ tion of anesthesia or to too much anesthetic agent in the absence of oxygen may be expected to behave in the same manner as the laboratory animal who is partially suf¬ focated deliberately and at the same time given epineph¬ rine experimentally to produce ventricular fibrillation or cardiac st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

1962
1962
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 3 publications
0
24
1
1
Order By: Relevance
“…Implantation bleeding was hypothesized by Speert and Guttmacher in 1954 [33], but a recent study of vaginal bleeding patterns in early pregnancy found “no support for the hypothesis that implantation can produce vaginal bleeding” [34]. Like the notion that pre-ejaculatory fluid can cause pregnancy, the idea of implantation bleeding seems to have been introduced by the medical profession itself.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation bleeding was hypothesized by Speert and Guttmacher in 1954 [33], but a recent study of vaginal bleeding patterns in early pregnancy found “no support for the hypothesis that implantation can produce vaginal bleeding” [34]. Like the notion that pre-ejaculatory fluid can cause pregnancy, the idea of implantation bleeding seems to have been introduced by the medical profession itself.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio was used to estimate relative risk. Ninety-five percent confidence limits were calculated using the Cornfield method ( 5 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Speert & Guttmacher (1954) found that 74% of a group who aborted within the first trimester had no nausea or vomiting whatever, compared with only 30% of a group who did not abort. A 2 test calculated by this author shows this to be a highly significant difference (p<0.001).…”
Section: Dependent Variablesmentioning
confidence: 94%